PENGARUH KOMPETENSI INDIVIDU TERHADAP KINERJA PENYULUH PERTANIAN (PETERNAKAN) DI KECAMATAN MAMUJU KABUPATEN MAMUJU - Rahmat Ihsan, Palmarudi Mappigau, Syahdar Baba (Jurnal Ilmu dan Industri Peternakan, 2015)
ABSTRACT. This study aims to determine the effect on the performance of individual competence agricultural extension (farms) in the district of Mamuju Mamuju. This is the kind of research that aims explanatory Quantitative explain the influence of independent variables on the dependent variable, in this case Pengauruh Individual Competence for Performance Agricultural Extension (Ranch) in the district of Mamuju Mamuju. This study was conducted in May 2014 in the district of Mamuju Mamuju. The location was chosen because of the growing information that the dynamic performance of agricultural extension/farms in conducting the intensity of assistance and dissemination to the farmer group was minimal. The analysis tool used is infrensial statistical data analysis tools (parametric) to see the effect of several variables indpenden (X) to the dependent variable (Y) by t test (partial) and F test (simultaneous). Based on the research showed that the variable skills (X1) had no significant effect on the performance of an extension, while the work ethic variable (X2) and motivation (X3) significantly affects the performance of a counselor in the district of Mamuju Mamuju. The biggest variable contribution to the performance extension that work motivation of 0.426 or 42.6%.